Association of the changes in pulmonary artery diameters with clinical outcomes in hospitalized patients with COVID-19 infection: A cross-sectional study - ILGIN, CAN; KARAKURT, SAİT (My University, 2022)
Objective: Enlarged pulmonary artery diameter (PAD) can be associated with mortality risk in coronavirus disease 2019 (COVID-19) patients. Our aim is to find the factors that cause changes in PAD and the relationship between radiological findings and clinical outcomes in COVID-19 patients.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Pulmonary artery diameter; COVID-19; Thromboembolism; CoRad; WHO score; COMPUTED-TOMOGRAPHY; LYMPHOCYTE RATIO; METRICS